Are Nine-Ending Prices Equally Influential in Eastern Culture for Pricing Green Products?. Issue 3 (27th May 2018) - Tripathi, Avinash; Pandey, Neeraj
ABSTRACT: This research offers some insights into applicability of nine-ending prices in Eastern culture for the pricing of green products. The research was accomplished through two experimental studies, the first experiment was designed as a 2 (nine-endings vs. control) × 2 (green vs. non-green) mixed design, and the second as a 3 (nine-endings, five-endings vs. control) × 2 (motivations: hedonic vs. utilitarian) between-subjects design. The results show that consumers do not favor nine-ending prices for green products. However, the consumers' varied product purchase motivations are found to have a significant influence on preference for particular price-endings, which have important practical implications.